Coaching and ethical self-creation: problematizing the "efficient tennis machine". Issue 1 (2nd January 2019) - Gerdin, Göran; Pringle, Richard; Crocket, Hamish
Abstract: In this paper we draw from Foucault, particularly his writings on the technologies of self, to problematize and reimagine understandings of what it means to coach effectively and ethically . In recognising the difficulty of operationalising Foucauldian ideas, we provide a narrative-of-self to reveal how an elite tennis coach, Göran Gerdin, adopted Foucauldian ideas in a process of ethical self-creation. The narrative reveals how Göran experienced the tragedy of youth player suicide and how he critically reflected on his coaching role in relation to this tragedy. Through specifically problematizing the insidious influence of technologies of dominance on athletic subjectivity, Göran reveals how he drew from Foucault to develop alternative coach practices and a related telos . We conclude by reflecting on pragmatic issues associated with coaching with Foucault.